2015
DOI: 10.1111/aor.12416
|View full text |Cite
|
Sign up to set email alerts
|

Biologic Response of Inguinal Hernia Prosthetics: A Comparative Study of Conventional Static Meshes Versus 3D Dynamic Implants

Abstract: Despite improvements in prosthetics and surgical techniques, the rate of complications following inguinal hernia repair remains high. Among these, discomfort and chronic pain have become a source of increasing concern among surgeons. Poor quality of tissue ingrowth, such as thin scar plates or shrinking scars-typical results with conventional static implants and plugs-may contribute to these adverse events. Recently, a new type of 3D dynamically responsive implant was introduced to the market. This device, des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 26 publications
2
26
0
2
Order By: Relevance
“…The hard, fibrotic plaque sharply contrasts with the highly motile behavior of the inguinal area, sometimes leading to painful impairment of groin movements. In literature, this feature is thought to be related to the static nature of the flat meshes which, incorporated by motionless and rigid tissue elements, impede the regular muscle function of the repaired groin . Furthermore, recent studies concerning the pathogenesis of hernia disease have demonstrated the degenerative source of inguinal protrusions .…”
mentioning
confidence: 99%
“…The hard, fibrotic plaque sharply contrasts with the highly motile behavior of the inguinal area, sometimes leading to painful impairment of groin movements. In literature, this feature is thought to be related to the static nature of the flat meshes which, incorporated by motionless and rigid tissue elements, impede the regular muscle function of the repaired groin . Furthermore, recent studies concerning the pathogenesis of hernia disease have demonstrated the degenerative source of inguinal protrusions .…”
mentioning
confidence: 99%
“…The concept of three-dimensional meshing without additional methods of fixation has gained popularity in human medicine in recent years. Fixation-free three-dimensional meshing induces ingrowth of viable and structured tissue instead of regressive fibrotic scarring causing pain, which is often encountered when fixed static implants are used [15]. Clinical outcome using this meshing concept was considered excellent in human inguinal hernia repair [16].…”
Section: Discussionmentioning
confidence: 99%
“…The estimated median dimension of the EF was 3 (2-4) fingers corresponding to a median circumference of 12 (8)(9)(10)(11)(12)(13)(14)(15)(16) cm measured on the fingers of a 7.5 gloved surgeon.…”
Section: Main Studymentioning
confidence: 99%
“…Recently, another hernia repair concept has been developed, concerning the obliteration of the hernia opening by means of 3D dynamic responsive implants [21e29]. The results of this technique seems to be effective in the treatment of combined hernia thanks to the probiotic biologic response that seems to address the degenerative pathogenesis of the inguinal protrusions [30].…”
Section: Discussionmentioning
confidence: 99%